Sustained Effectiveness of a Mandatory Employee Influenza Vaccination Policy at a Cancer Center - Mahoney, Martin C.; Kozakiewicz, Janice; Ray, Andrew D. (Scientific Research, 2014)
Objectives: Despite the well-known advantages associated with immunization, it has proven difficult to achieve high levels of influenza vaccination among Health Care Professionals (HCPs). This report describes results of an influenza vaccination program implemented within a comprehensive cancer center. Methods: Using records from calendar years 2005-2013, we completed a retrospective analysis of annual influenza vaccination rates at this center. A mandatory influenza vaccination policy was implemented in 2010, while prior to that vaccination was encouraged but not required. Vaccinations are free to employees and distributed at various locations. Annual influenza vaccination rates were examined by calendar year and by occupational group (medical, nursing, administrative, scientific, other support staff). Results: High levels of adherence with the mandatory influenza policy were observed for all employee groups. Prior to influenza vaccine mandates flu vaccination rates ranged from ~30% - 40% and increased to 85% - 89% with the mandate. Conclusions: Robust influenza vaccination rates have been sustained since implementation of a vaccination mandate supporting further expansion of policies requiring influenza vaccination for HCPs.
Keywords: Influenza; Vaccination; Occupational Health; Health Care Workers; Mandatory Program; Health Policy